Assembly of high nuclearity clusters from a family of tripodal tris-carboxylate ligands - Argent, Stephen P.; Tarassova, Irina; Greenaway, Alex; Nowell, Harriot; Barnett, Sarah A.; Warren, Mark R.; Tang, Chiu C.; Morris, Christopher G.; Lewis, William; Champness, Neil R.; Schröder, Martin; Blake, Alexander J. (Elsevier, 2016)
A family of four tris-carboxylic acid ligands 1,3,5-tris(4′-carboxybiphenyl-2-yl)benzene (H3L1), 1,3,5-tris-2-carboxyphenylbenzene (H3L2), 1,3,5-tris(4″-carboxy-para-terphenyl-2-yl)benzene (H3L3) and 1,3,5-tris(3′-carboxybiphenyl-2-yl)benzene (H3L4) have been synthesised and reacted with first row transition metal cations to give nine complexes which have been structurally characterised by X-ray crystallography. The ligands share a common design motif having three arms connected to a benzene core via three ortho-disubstituted phenyl linkers. The ligands vary in length and direction of the carboxylic acid functionalised arms and are all able to adopt tripodal conformations in which the three arms are directed facially. The structures of [Zn8(μ4-O)(L1)4(HCO2)2(H2O)0.33(DMF)2] (1a-Zn), [Co14(L2)6((μ3-OH)8(HCO2)2(DMF)4(H2O)6] (2-Co), [Ni14(L2)6(μ3-OH)8(HCO2)2(DMF)4(H2O)6] (2-Ni), [Zn8(μ4-O)(L3)4(DMF)(H2O)4(NO3)2] (3-Zn), [Ni5(μ-OH)4(L2)2(H2O)6(DMF)4] (5-Ni), [Co8(μ4-O)4(L4)4(DMF)3(H2O)] (6-Co) and Fe3(μ3-O)(L4)2(H2O)(DMF)2)] (7-Fe) contain polynuclear clusters surrounded by ligands (L1–4)3− in tripodal conformations. The structure of [Zn2(HL1)2(DMF)4] (1b-Zn) shows it to be a binuclear complex in which the two ligands (HL2)2− are partially deprotonated whilst {[Zn3(L2)2(DMF)(H2O)(C5H5N)]·6(DMF)}n (4-Zn) is a 2D coordination network containing {Zn2(RCO2)4(solv)2} paddlewheel units. The conformations of the ligand arms in the complexes have been analysed, confirming that the shared ortho-disubstituted phenyl ring motif is a powerful and versatile tool for designing ligands able to form high-nuclearity coordination clusters when reacted with transition metal cations.